Evaluation of multi‐use stormwater detention basins for improved urban watershed management. Issue 3 (20th December 2012) - Park, Daeryong; Jang, Sukhwan; Roesner, Larry A.
Abstract Detention basins are used to capture postdevelopment runoff and control the peak discharge of the outflow using orifices and weirs. The use of detention basins is typical practice in the construction of new developments on the fringe of existing urban areas, such as the Ulsan–Hwabong district in the city of Ulsan, South Korea. In this study, the required volume and flooding area of a detention basin was determined to control development outflow peaks for 2‐year, 10‐year, and 100‐year design storms with type II rainfall distributions as characterized by the US Department of Agriculture's Soil Conservation Service method. The rainfall–runoff simulation model used was the US Environmental Protection Agency's Storm Water Management Model (EPA‐SWMM) 5, which is the latest version of the software, updated for Windows. We designed three cases of detention basins multi‐staged by 2‐year, 10‐year, and 100‐year design storms and verified the designs with the application of 49 years (1961–2009) of hourly historical rainfall data. The three detention basin designs were compared in terms of the total construction and land costs as well as the benefits associated with recreational facilities or parking lot use. As a result, the design sizes of the detention basins are slightly greater than the actual sizes needed based on the historical rainfall application. Multi‐use detention basins (MDBs) based on 2‐year and 10‐year design storms were found to yield 37.4% and 22.8% benefits, respectively, for recreational facility use compared with detention basins without multi‐use space, and the results also indicate that benefits accrue after 6.5 years for parking lot use. The results of this study suggest that an MDB based on a 2‐year design storm is the most cost‐effective design among the three cases considered for Ulsan, South Korea. Copyright © 2012 John Wiley & Sons, Ltd.